A four-beam pattern reconfigurable Yagi-Uda antenna - Kittiyanpunya, C.; Krairiksh, M. (My University, 2013)
This communication presents a pattern reconfigurable antenna which is based on the Yagi-Uda configuration that can change the radiation beam into four directions. The function of the parasitic elements can be altered between a director and a reflector with PIN diodes while the driven element can be altered between two perpendicular directions with RF switches. To be able to use this proposed antenna on an electric conductor, such as on the vehicle rooftop, the antenna is thus mounted on electromagnetic band gap (EBG) structure which serves as a magnetic conductor. The gain is approximately 5 dBi and the field trial exhibited the diversity gain of 17 dB over the fixed beam antenna. As a result, the proposed antenna possesses high potential for further development into a TV signal reception on moving vehicles. © 2013 IEEE.
Keywords: EBG; Magnetic conductor; Mobile TV antenna; Pattern reconfiguration; PIN diode; Reconfigurable antenna; RF switch; Yagi-Uda antenna